Basal complex: a smart wing component for automatic shape morphing - Sepehr H. Eraghi; Arman Toofani; Ramin J. A. Guilani; Shayan Ramezanpour; Nienke N. Bijma; Alireza Sedaghat; Armin Yasamandaryaei; Stanislav Gorb; Hamed Rajabi (Communications Biology, 2023)
Abstract Insect wings are adaptive structures that automatically respond to flight forces, surpassing even cutting-edge engineering shape-morphing systems. A widely accepted but not yet explicitly tested hypothesis is that a 3D component in the wing’s proximal region, known as basal complex, determines the quality of wing shape changes in flight. Through our study, we validate this hypothesis, demonstrating that the basal complex plays a crucial role in both the quality and quantity of wing deformations. Systematic variations of geometric parameters of the basal complex in a set of numerical models suggest that the wings have undergone adaptations to reach maximum camber under loading. Inspired by the design of the basal complex, we develop a shape-morphing mechanism that can facilitate the shape change of morphing blades for wind turbines. This research enhances our understanding of insect wing biomechanics and provides insights for the development of simplified engineering shape-morphing systems.